An evaluation of hepatitis C knowledge and correlations with health belief model constructs among African American "baby boomers" - Mohamed E. Rashrash; Mary K. Maneno; Anthony K. Wutoh; Earl B. Ettienne; Monika N. Daftary (Elsevier, 2016)
Summary: Background: Baby boomers (people born between 1945 and 1965) are responsible for three-quarters of Hepatitis C (HCV) infections in the US; however, HCV testing is distinctly underused by them. Aim: To assess the status, predictors, and correlates of HCV knowledge among African-American baby boomers (AABBs) in Washington, DC. Methods: A cross-sectional survey among persons aged 46-69 was conducted using audio computer-assisted self-interviewing (ACASI). Data on HCV knowledge, socio-demographics, prior history of HCV testing, health-related characteristics, HCV vulnerability and HCV treatment perceptions were collected. Descriptive statistics was used to describe the study population. Pearson correlations were used to examine linear associations between HCV knowledge and Health Belief Model constructs related to HCV. Linear regression analysis was conducted to assess the predictors of knowledge. Results: Out of the 137 participants, about sixty percent (60.6%) were females, mean age 59 ± 6.40; 44.8% had at least a college education. The average knowledge score was low (48.7%). HCV knowledge was significantly correlated with constructs of perceived severity and perceived benefits. Age (β = −0.10; p = 0.003), and level of education (β = 0.93, p = 0.027) were significant predictors. Conclusions: Overall, respondents have a low level of knowledge. The lower level of education and older age were significant predictors of inadequate HCV knowledge. Thus, HCV education among these people may be a vital component in reducing the gaps in HCV knowledge. Keywords: Baby boomer, Health Belief Model, Hepatitis C, Knowledge